Site-Based Conservation of Terrestrial Bird Species in the Caribbean and Central and South America Under Climate Change - Voskamp, Alke; Butchart, Stuart H. M.; Baker, David J.; Wilsey, Chad B.; Willis, Stephen G. (Frontiers in Ecology and Evolution, 2021)
Two of the principal responses of species to recent climate change have been changes in range and abundance, leading to a global reshuffling of the geographic distribution of species. Such range changes may cause species to disappear from areas they currently occupy and, given the right conditions, to colonize new sites. This could affect the ability of site networks (such as protected areas) to conserve species. Identifying sites that will continue to provide suitable conditions for focal species under future climate change scenarios and sites that are likely to become unsuitable is important for effective conservation planning. Here we explore the impacts of climate change on terrestrial bird species of conservation concern in the Neotropics, and the consequences for the network of Important Bird and Biodiversity Areas (IBAs) identified to conserve them. We modelled changes in species distributions for 3,798 species across the Caribbean and Central and South America, accounting for species-specific biological traits (natal dispersal ability and generation length), to assess species occurrences across the IBA network under different future climate scenarios. Based on the projected changes in species compositions, we identify potential management strategies across the IBA network. We project that future climate change will have substantial impacts on the distribution of individual species across the IBA network, resulting in very heterogenous impacts on the individual IBAs. Mean turnover of species of conservation concern across the IBA network was 17% by 2050. Nonetheless, under a medium-warming scenario, for 73% of the 939 species of conservation concern for which IBAs have been identified, more than half of the IBAs in which they currently occur were projected to remain climatically suitable, and for 90% at least a quarter of sites remain suitable. These results suggest that the IBA network will remain robust under climate change. Nevertheless, 7% of the species of conservation concern are projected to have no suitable climate in the IBAs currently identified for them. Our results highlight the importance of a network-wide perspective when taking management decisions for individual sites under climate change.